The effect of lean and agile supply chain strategy on financial performance with mediating of strategic supplier integration & strategic customer integration: Evidence from bottled drinking-water industry in Indonesia - Gede Ariadi; Surachman; Sumiati; Fatchur Rohman (Cogent Business & Management, 2021)
This study analyses the importance of lean supply chain strategy (SCS) and agile SCS in Indonesia's bottled water industries, influencing the financial performance through mediating variables. Using the resource-based view (RBV) theory and relational view to investigate these relations, a series of hypotheses are developed, considering strategic supplier integration (SSI), strategic customer integration (SCI) as a mediator variable. The study analyses structural equation modeling (SEM) derived by observed data from 139 firms in Indonesia. The research analyzes how lean SCS and agility SCS on financial performance is affected by SSI and SCI. The paper supports the literature on lean SCS and agile SCS by theoretically elucidating and empirically revealing how SSI and SCI collaborating affect a positive relationship between lean SCS & agile SCS and financial performance.
Keywords: 650; Business; Management and Accounting; Production; Operations & Information Management; Supply Chain Management